The Interaction of Learning Model and Learning Style in Improving Students Learning Outcomes (Journal of Primary Education, 2019)
The purpose of this study was to determine the interaction between learning models (problem-based learning and inquiry-based learning) and learning styles in improving students learning outcomes (cognitive, affective, and psychomotor). The research method applied in this study was quantitative descriptive by using data analysis techniques of validity test, reliability test, difficulty level test, normality test, homogeneity test, and two-way ANOVA test. The data collection techniques used were tests in the form of descriptive questions, and non-tests in the form of cooperative attitude observation sheets, and student learning style questionnaire sheets. The subjects in this study were 48 students who were divided into two groups. The first group consisted of 24 students using the problem-based learning model, and the second group consisted of 24 students using the inquiry-based learning model. The results of the study showed that: There is an interaction between learning models and learning styles in improving the learning outcomes in the cognitive and affective domains. There is no interaction between learning models and learning styles in improving psychomotor domains. The learning model of inquiry-based learning was more effective to be used in the learning than the problem-based learning models in improving student learning outcomes (cognitive, affective, and psychomotor) in the class with heterogeneous student learning styles (visual, auditory, and kinesthetic).